Pulmonary effects of exposures in silicon carbide manufacturing. Issue 1 (February 1984) - Peters, J M; Smith, T J; Bernstein, L; Wright, W E; Hammond, S K
Abstract : Chest x rays, smoking histories, and pulmonary function tests were obtained for 171 men employed in the manufacturing of silicon carbide. A lifetime exposure to respirable particulates (organic and inorganic fractions) and sulphur dioxide was estimated for each worker. Chest x ray abnormalities were related to respirable particulates (round opacities) and to age and smoking (linear opacities). Pulmonary function was affected by respirable particulates (FVC) and by sulphur dioxide and smoking (FEV1). Pleural thickening was related to age. No exposures exceeded the relevant standards; we therefore conclude that the current standards do not provide protection against injurious pulmonary effects, at least in this industry.